The potential effect of silver nanoparticles to inhibit microbial activity in orthodontic adhesive appliances: A literature review - Silviana, Nur Masita; Fariha, Safira; Permata, Shevya Nanda Indika; Utomoputri, Tasya Safina; Pramadita, Thessalonica; Sukadi, Zefanya Nicko (Insisiva Dental Journal: Majalah Kedokteran Gigi Insisiva, 2024)
Silver nanoparticles have been the focus of research in various areas of dentistry, including orthodontics. Orthodontic treatment requires a long period of time, so the brackets are in the oral cavity for a long time. This can potentially trigger the formation of white spot lesions because plaque sticks more easily to the surrounding enamel. Using silver nanoparticles mixed with orthodontic adhesives has been reported to increase antibacterial and antimicrobial characteristics. This literature review aims to investigate the effect of adding silver nanoparticles to orthodontic adhesive devices in inhibiting antimicrobial activity. This study method was carried out by searching the online electronic databases PubMed, Science Direct, and Google Scholar with the keywords "silver nanoparticles AND antimicrobial", "silver nanoparticles AND orthodontic adhesive", "silver nanoparticles AND composite resin", which is an original article published the year 2019- 2023. The results of research from 10 articles that met the inclusion criteria showed that orthodontic adhesives with silver nanoparticles effectively inhibited microbial activity, such as Streptococcus mutans (S.mutans), Lactobacillus acidophilus (L.acidophilus), Streptococcus sanguinis (S.sanguinis) and Candida albicans through increased release of Ag+ ions. Silver has been known to have effects, including producing minimal bacterial resistance compared to antibiotics. Even though it results in a decrease in the shear bond strength (SBS), the decrease level is still within clinically tolerable limits. It can be concluded that research needs to continue to be developed to obtain the right concentration and composition of the addition of silver nanoparticles so that an orthodontic adhesive material is obtained that is not only superior in its antibacterial properties but also in its mechanical properties.